10.2 Operations on Functions


f(x)=−3x2+3x
g(x)=2x+5
Find f(−4)÷ g(−4)


 


 


 


 


 


 


 


 


 


 

h(n)=2n−1
g(n)=3n −5
Find h(0)÷ g(0)


 


 


 


 


 


 

g(x)=−4x+1
h(x)=−2x −1
Find g(5)+h(5)


 


 


 


 


 


 


 


 

g(a)=3a−2
h(a)=4a−2
Find (g +h) (−10)


 


 


 


 


 


 

g(x)=x+3
f(x)=−x+4
Find (g − f)(3)


 


 


 


 


 


 


 

h(t)=t+5
g(t)=3t−5
Find (h · g)(5)


 


 


 


 


 


 

f(n)=n −5
g(n)=4n+2
Find (f + g)(−8)


 


 


 


 


 

f(x)=3x −4
g(x)=x3+2x2
Find (f * g)(x)


 


 


 


 


 

g(a)=a3+5a2
f(a)=2a+4
Find g(3)+ f(3)


 


 


 


 


 


 


 

g(a)=3a+3
f(a)=2a−2
Find (g + f)(9)